Unemployment Alleviation Strategy Through The Implementation of Zakat Commandment - Syamsuri, Syamsuri; Mabarroh, Inda Taqiya; Nurfattah, Arizqiya; Shuib, Mohd Sollehudin (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
Zakat has an important role as an instrument to realize income equality and maintain balance in society, one of which is overcoming unemployment. This research aims to find out how the strategy of distributing zakat funds can alleviate unemployment by Islamic law. This research examines the theoretical relationship between the pattern and mechanism of zakat management, viewed from a sharia perspective, and its economic impact. This is literature research by reviewing books and journals discussing productive zakat in poverty alleviation efforts. This study is a descriptive comparative analysis. The data collected is analyzed using the content analysis method, a technique used to analyze the meaning of the data collected through literature research. The results of this study indicate that the role of zakat in overcoming unemployment is getting better economically through the distribution of consumptive zakat. The consumptive assistance will increase Mustahik's purchasing power to meet their needs. The increase in purchasing power has a positive impact on increasing a company's production. With the increasing demand for the product, companies need to improve their production capacity. The company will hire more labour to meet the increased demand, and consequently, the problem of unemployment can be overcome